반려견 팬텀에서 유방암 근접방사선치료 시 흡수선량 평가 - 김정훈; Jung-hoon Kim; 이득희; Deuk-hee Lee (한국방사선학회 논문지, 2020)
반려견의 사망원인 1위인 암 중 암컷에게서 가장 높은 발생률을 보이는 유방암을 대상으로 근접방사선 치료 수행 시 모의모사를 이용한 흡수선량 측정을 바탕으로 적용성을 평가하고자 하였다. 모의모사를 위해 MCNPX 프로그램을 이용하였으며, 흡수선량 측정을 위해 소형견 크기의 수학적 팬텀을 제작 하였다. 흡수 선량 측정결과 종양의 경우 192 Ir에서 1.02E-12 Gy/#으로 흡수선량이 가장 높은 것으로 나타났으며, 내·외부 흡수선량에서도 동일한 경향성으로 나타났다. 따라서 반려견 유방암의 근접방사선치료 시 견종과 피폭을 고려한 적절한 선원의 선택이 고려되어야 될 것이다. The application of breast cancer, which has the highest incidence in females among cancer that is the number one cause of death for dogs, was to be evaluated the absorbed dose during brachytherapy using simulation. MCNPX program was used for simulation, and a small size canine phantom was produced to measure absorbed dose. The results of the absorbed dose was the highest at 192 Ir to 1.02E-12 Gy/# for tumors, and the same tendency was shown for internal and external absorbed dose. Therefore, the selection of appropriate sources for dog breast cancer should be considered in brachytherapy, taking into account dog breeds and exposures.